Sharka, a vector-borne disease caused by Plum pox virus: vector species, transmission mechanism, epidemiology and mitigation strategies to reduce its natural spread - Cambra, Mariano; Vidal, Eduardo (ISHS, 2020)
Most plant viruses (90%) depend on insect vectors for transmission. Plum pox virus (PPV) is a non-persistent (stylet-borne) aphid-transmitted pathogen, the only stone-fruit virus that spreads by aphids. This transmission is an active process that requires first an aphid species able to acquire the virus in a few seconds from an infected cell, then retention of the virus for a few hours, but a latent period is not required for success in inoculation of a healthy plant cell by an egestion-ingestion mechanism. Electronic devices can distinguish between intercellular and intracellular environments, and the electrical penetration graphs (EPG) technique records the aphid's alimentary behaviour (i.e., E1 phloem salivation linked to virus inoculation and E2 phloem ingestion linked to virus acquisition). The HC-Pro virus-encoded helper component acts as a bridge between specific receptors located in the vector's cuticula and the virus. Population dynamics of parthenogenetic aphid females reach important peaks from early spring to the beginning of summer according to the latitude, altitude and specific climatic conditions of each year. Migrant species are more efficient in PPV spread than those that colonize Prunus species. Of the 28 described PPV-vector species, the main ones are Aphis spiraecola (in Mediterranean temperate climates), Phorodon humili and Hyalopterus pruni (in continental climates) and Myzus persicae, rarely present in both areas. Vector intensity is a product of propensity and activity that can be used for modelling and to predict outbreaks. The large number of PPV RNA targets inoculated by an M. persicae aphid in a single probe (average ~26,750) was responsible for a systemic infection of 20% of the inoculated GF305 peach seedlings and, consequently, may cause sharka outbreaks related to the available inoculum. Sticky plant traps and squash real-time RT-PCR can accurately estimate the percentage of individual aphids carrying PPV targets that visit a tree. Spatial and temporal patterns of PPV natural spread have been established in different ecological areas. A single aphid can transmit one or more PPV strains simultaneously. Measures against vector activity and transmission are the most successful strategies to mitigate virus epidemics. Reducing vector populations by insecticide treatments is not the best control strategy, because, during the very brief probing activities, PPV is inoculated more quickly than the time needed for insecticides to kill the vector. Treatments are effective at reducing only colonizing aphid species. The use of virus-free plantation material and removal of sources of inoculum into the crop are effective measures, as well as the use of physical barriers (e.g., plastic insect-proof covers, screens with microencapsulated pesticides, mineral oil treatments) and PPV-resistant cultivars to interfere with transmission.